La teoría del ciclo vital de Franco Modigliani: enfoque en los salarios de los trabajadores colombianos (2017)
The life cycle theory of Franco Modigliani studies salary, savings and future consumption about age and the labor market. This theory establishes that there are more significant savings in the early stages of life and a dissaving at the end of the life cycle. According to the author, the income of the people who are in the average number of workers that retire from the labor market tends to decrease as the worker ages. Regarding the employed population, the empirical facts show that the wage of workers increases until reaching a maximum, which falls after retirement, thus fulfilling Modigliani’s theory.